2014
DOI: 10.1016/j.ebcr.2014.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Focal epilepsy presenting as a bath-induced paroxysmal event/breath-holding attack

Abstract: Bath-induced paroxysmal events in infants and children can be triggered by various etiologies, including cardiological, neurological, and metabolic causes. It is important to ascertain the underlying cause for such events as this significantly affects the child's management and prognosis. We present the case of a 19-month-old boy who presented with recurrent episodes of apnea, cyanosis, and reduced level of consciousness in response to bathing. Through detailed history and investigation, the diagnosis of water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…In our case, clinical features and EEG ictal findings were consistent with bathing epilepsy. The differential diagnosis of bathing epilepsy is complex and a comprehensive workup, including a video-EEG recording of the seizures during bathing, is necessary to exclude non-epileptic events or other epilepsy syndromes [2,3]. The prognosis of bathing epilepsy is usually benign.…”
Section: Discussionmentioning
confidence: 99%
“…In our case, clinical features and EEG ictal findings were consistent with bathing epilepsy. The differential diagnosis of bathing epilepsy is complex and a comprehensive workup, including a video-EEG recording of the seizures during bathing, is necessary to exclude non-epileptic events or other epilepsy syndromes [2,3]. The prognosis of bathing epilepsy is usually benign.…”
Section: Discussionmentioning
confidence: 99%
“… 43 Children with this condition may develop constipation in an attempt to prevent pain attack. 44 The attacks of pain that occur with these young children may be also associated with seizures, 45 slowed heartbeat 2 and apnea. 46 As the children get older, the pain location seems to change, switching from the lower portion of the body to affecting mostly the face and the head with the pain being focused on the eyes and the jaws.…”
Section: Paroxysmal Extreme Pain Disordermentioning
confidence: 99%
“…This contradicts the findings of our very careful review [2] , which found only four conditions triggered by bathing in infants, these being bathing epilepsy — by far the commonest [2] , [3] , [4] , [5] , alternating hemiplegia of childhood [6] , hyperekplexia, and paroxysmal extreme pain disorder [2] . Stutchfield and Loh [1] stated that reflex anoxic seizures (reflex asystolic syncope), cyanotic breath-holding spells (prolonged expiratory apnea), and cardiac syncope from long QT syndrome might be triggered by bathing in infancy, but to my knowledge, no such reports have been published.…”
mentioning
confidence: 97%
“…I was interested to read the case report of bathing epilepsy published by Stutchfield and Loh [1] and wish to comment on several misleading statements and factual errors. As the authors would know, we have published a comprehensive review of bath-induced events [2] .…”
mentioning
confidence: 99%
See 1 more Smart Citation